Valganciclovir for the Prevention of Complications of Late Cytomegalovirus Infection after Allogeneic Hematopoietic Cell Transplantation: A Randomized Controlled Trial - Boeckh, Michael (Ann Intern Med, 2015)
BACKGROUND: Optimal prevention of late cytomegalovirus (CMV) disease remains poorly defined. OBJECTIVE: To compare valganciclovir prophylaxis with PCR-guided preemptive therapy. DESIGN: Randomized, double-blind trial. Patients were randomized to valganciclovir or placebo. ClinicalTrials.gov registration number: NCT00016068 SETTING: Multicenter trial involving 8 centers. PATIENTS: 184 HCT recipients at high risk for late CMV disease (valganciclovir N=95, placebo N=89). INTERVENTIONS: 6 months of valganciclovir (900 mg/day) or placebo. Patients with PCR positivity at ≥ 1000 copies/mL (1000 IUs/mL) were treated with ganciclovir or valganciclovir (5 mg/kg or 900 mg twice daily, respectively). Hematopoietic growth factors were prescribed for neutropenia. MEASUREMENTS: Composite primary endpoint was death or CMV disease or other invasive infections by day 270 after HCT. Secondary endpoints were CMV disease, CMV DNAemia, death, other infections, resource utilization, ganciclovir resistance, quality of life, immune reconstitution, and safety. RESULTS: The primary composite outcome occurred in 20% of valganciclovir vs. 21% of placebo-preemptive therapy) recipients (treatment difference −0.01, 95% confidence interval −0.13, 0.10, P=0.86). There was no difference in the primary endpoint and its components at day 640 after HCT. CMV DNAemia ≥ 1000 copies/mL was reduced in the valganciclovir group (11% versus 36%, P < 0.001). Neutropenia was not significantly different at the absolute neutrophil count level of <0.5 × 10(9) per L (P=0.57), however, more subjects received hematopoietic growth factors in the valganciclovir group (25% versus 12%, P=0.026). No statistically significant differences were observed in other secondary outcomes. LIMITATIONS: Some high-risk patients were not included. CONCLUSIONS: Valganciclovir prophylaxis did not improve the CMV disease- free and invasive infection-free survival composite endpoint when compared to PCR-guided preemptive therapy. Both strategies performed similarly with regard to most clinical outcomes. PRIMARY FUNDING SOURCE: Roche Laboratories